Biomaterials used in the conservative treatment of pulp tissue - Bueno, Carlos Roberto Emerenciano [UNESP]; Cury, Marina Tolomei Sandoval [UNESP]; Vasques, Ana Maria Veiga [UNESP]; Silva, Ana Cláudia Rodrigues [UNESP]; Cosme-Silva, Leopoldo (My University, 2022)
Conservative treatments aim to preserve pulp vitality. Over the years, several materials have been used for direct pulp capping, indirect pulp capping and pulpotomy. Accurate diagnosis at the time of treatment, although still a challenging task in primary teeth, is yet an essential requirement. The type and quality of the restoration also influences the success rate as does the clinician's experience. The knowledge acquired over the years allowed scientists to have a better understanding of the biological processes behind the interactions of living tissues with dental materials. Therefore, materials that undergo direct contact with living tissue should present biocompatible features, besides the ability to induce deposition of mineralized hard tissue. This chapter discusses dental materials used in the conservative treatment of pulp tissue, starting from a brief description of pulp tissue composition, techniques used in vital pulp conservative therapy and a historic overview of materials used in management of vital pulp, from empirical materials to a new generation of bioactive materials.
Keywords: Bioactive materials; Conservative treatment; Dental pulp; Endodontics; Oral health